Media Podcast terhadap Kemampuan Menyimak - muhammad asrul sultan; alfianti akhmad; Nurabidah Idrus (Universitas Negeri Makassar, 2020)
The objective of this research was to determine the effect of podcast media on the listening comprehension on subjects Bahasa Indonesia in class IV SD Negeri Parepare. This research uses a quantitative approach to the type of experimental research and uses the Quasy Experimental design in the form of The Nonequivalent Pretest-Posttest Control Group Design. The sampling technique used was purposive sampling with a sample of 46 students. Data collection techniques used in this research are tests in the form of multiple choices and documentation. Data analysis used descriptive statistical analysis techniques and inferential statistical analysis techniques. In testing the hypothesis in inferential statistical analysis using the Paired Sample T-test. The result is that podcast media affects the increase in listening comprehension on subjects Bahasa Indonesia in class IV SD Negeri 55 Parepare.